Pengaruh Kredit Usaha Rakyat (KUR), Total Aset, Jumlah Tenaga Kerja, Biaya Pemasaran Dan Lokasi Usaha Terhadap Pendapatan Usaha Mikro Kecil dan Menengah (UMKM) Berbasis Ekonomi Kreatif di Kota Semarang - Meilinda, Devi; Mahmud, Amir (Business and Accounting Education Journal, 2020)
Micro Small and Medium Enterprises (MSMEs) is one solution of theeconomic system that is not alike at all global impact that hit the world including one of them is creative economy-based MSMEs in Semarang City. The purpose of this study is to determine whether there is influence of people's business credit, total assets, the amount of labor, marketing costs and location of business to revenue-based MSMEs creative economy in the city of Semarang.The population in this study is all MSMEs in Semarang City as much as 7015. The sample of this study was taken above the suggestion of sampling from Roscue that is minimalubs 60 respondents. Data method using questionnaire. The method used is descriptive statistics and multiple linear regression.The results showed that: (1) the variable of People's Business Credit (KUR), total assets, total labor and marketing costs partially affect MSME income, (2) business location partially has no effect on MSME income, (3) simultaneously People's Business Credit (KUR), total assets, number of workers, marketing costs and business location affect the income of MSMEs.